Analysis of Math Teacher Candidates’ Misconception on the Dynamic Electricity Concept - Dede Trie Kurniawan; Sri Maryanti (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
This study was intended to reveal the profile of students’ misconception of the concept of  dynamic electricity in one private university in Cirebon city. In the study of physics, the  misconception will hamper the achievement of physics learning goals. Misconceptions will greatly hinder the process of acceptance and assimilation of knowledge in students, so that they will hinder the success to learn more. It is necessary to conduct research on the analysis of misconception of mathematics teacher candidates on the concept of dynamic electricity. Misconception is defined as a student conception that is incompatible with the simplified conception of physicists. To identify misconceptions experienced by students, multiple-choice diagnostic tests equipped with a Certainty Response Index (CRI) can be conducted. The data obtained is then completed with interview data. This research is a descriptive research which is a research to give a description about phenomenon, or facts under study by describing the value of the variable without comparing. The study found that 81% of students’ have a misconception in the sub-chapter of electric current, and 50% in the concept of electric potential difference sub-chapter.